Direct Graphene Synthesis on Lithium Niobate Substrate by Carbon Ion Implantation - Xu, Yuhang; Lu, Fei; Liu, Kaijing; Ma, Changdong (Frontiers in Materials, 2020)
A dozen-micron-scale 4-7 layers of graphene was synthesized directly on Lithium Niobate (LiNbO3, LN) by carbon implantation in nickel covered LiNbO3 film. The 1.52E16 ions·cm-2 carbon ions of 80KeV were implanted to the nickel film with the implantation depth of 100nm, which is close to the interface between the nickel film and LiNbO3. The implanted carbon atoms dissolved in nickel at an elevated temperature and diffused towards to the interface between nickel film and LiNbO3 during annealing. After the nickel film fell off, the graphene material was found by Raman spectroscopy and confirmed by the Atomic Force Microscope (AFM) topographic image. Implantation combined with patterned metal film suggests the possibility to engineer two-dimensional graphene with special confinement. It also provides a valuable and novel way for integrating graphene-wafer structure for other available substrate wafer in microelectronics and photonics devices.